Płodowy zespół alkoholowy (FAS) jako zagrożenie dla rozwoju dziecka = Fetal alcohol syndrom (FAS) as threat to a child’s development - Baranowska, Aneta Sylwia (Journal of Education, Health and Sport, 2016)
Baranowska Aneta Sylwia. Płodowy zespół alkoholowy (FAS) jako zagrożenie dla rozwoju dziecka = Fetal alcohol syndrom (FAS) as threat to a child’s development. Journal of Education, Health and Sport. 2016;6(3):148-158. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47948 http://ojs.ukw.edu.pl/index.php/johs/article/view/3431 https://pbn.nauka.gov.pl/works/721363 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 20.03.2016. Accepted: 20.03.2016. PŁODOWY ZESPÓŁ ALKOHOLOWY (FAS) JAKO ZAGROŻENIE DLA ROZWOJU DZIECKA FETAL ALCOHOL SYNDROM (FAS) AS THREAT TO A CHILD’S DEVELOPMENT Aneta Sylwia Baranowska1 1Uniwersytet im. Adama Mickiewicza w Poznaniu; Wydział Studiów Edukacyjnych; e-mail: anet.bar@gmail.com Streszczenie Celem artykułu jest dokonanie charakterystyki płodowego zespołu alkoholowego, będącego konsekwencją spożywania przez matkę alkoholu w trakcie ciąży. Badania eksperymentalne wykazały, że alkohol etylowy przenika swobodnie przez barierę łożyskową z organizmu matki do krwiobiegu płodu, intensyfikując ryzyko powstania tzw. poalkoholowego spektrum zaburzeń rozwojowych (fetal alkohol spectrum disorder), w skrócie FASD. Jednym z nich jest płodowy zespół alkoholowy (fetal alkohol syndrom), przejawiający się u dzieci odmiennością w budowie ciała oraz zaburzeniami funkcjonowania. Bardzo ważna jest jego wczesna diagnoza, a w przypadku jego rozpoznania skuteczna pomoc psychologiczno-pedagogiczna dzieciom nim dotkniętym. Słowa klucze: poalkoholowe spektrum zaburzeń rozwojowych, płodowy zespół alkoholowy, diagnoza, pomoc psychologiczno-pedagogiczna, profilaktyka. Summary The aim of this article is to characterize fetal alcohol syndrom (FAS), which is a consequence of drinking alcohol during pregnancy by a mother. Experimental research has shown that ethanol crosses the placenta barrier between a mother and a child's blood circulation, intensifying the risk of fetal alcohol spectrum disorder, in short FASD. One of the disorder is fetal alcohol syndrom which manifests itself in difference in body composition and functioning disorders. Early diagnosis is extremely important, as well as effective psychological and pedagogical help for the children diagnosed with FAS. Key words: fetal alcohol spectrum disorder, fetal alcohol syndrom, psycho-pedagogical help, diagnosis, prevention.